A case of migraine treatment in a patient with a clinical diagnosis of CHARGE syndrome using onabotulinum toxin A. Issue 8 (18th May 2021) - Morrison, Julia B.; Fisher, Bradley M.; Arra, Angela; Bezuhly, Michael; Blake, Kim
Abstract: CHARGE syndrome is a genetic disorder that affects multiple organ and sensory systems. Cranial nerve involvement is one of the key clinical diagnostic criteria. We present the case of an 8‐year‐old girl with CHARGE syndrome, associated right‐sided facial palsy, and chronic severe migraines, that were intractable to medical treatment. At age 6, onabotulinum toxin A was used to weaken the contralateral non‐paralyzed side of her face to address her stigmatizing asymmetry. Onabotulinum toxin A chemodenervation was performed on the left lower lip depressors to relax the muscles and improve left lower lip position. Coincidentally, it was noted that with these treatments, migraine symptoms resolved. As the chemodenervation subsided over the next 3–4 months, the severe migraines returned. Continued treatment with onabotulinum toxin A injections every 3 months has resulted in ongoing improvements in facial symmetry and migraine control. Onabotulinum toxin A is a well‐known treatment of chronic migraine. Injections are usually directed to the occipitalis, frontalis, and corrugator muscles. The literature has no reports of injections to the lower lip depressors as a useful therapy for migraine, making the results from this case unique.